PERBANDINGAN PENGARUH STRATEGI PEMBELAJARAN INDEX CARD MATCH DENGAN GIVING QUESTIONS AND GETTING ANSWERS TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 3 TANJUNG RAJA - Laila Eprilia; Siti Fatimah; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This research aims to know about comparison effect of learning strategy of Index Card Match with Giving Questions and Getting Answers to students' learning outcomes on economic subjects in SMA Negeri 3 Tanjung Raja. The problem formulation is